1977
DOI: 10.1520/jfs10375j
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem Pink Teeth

Abstract: The observation, in 1953, of pink-colored teeth in the exhumed body of a victim in the Christie murders appears to have been the first report of this postmortem phenomenon in recent times [1]. In reporting this and four other cases, Miles and Fearnhead [2] suggested that the pinkness is a natural postmortem phenomenon caused by the seepage into the dentinal tubules of a fluid containing hemoglobin or its degradation products derived from decomposition or liquefaction of the tooth pulp. Beeley and Harvey [3] fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 2 publications
1
30
0
1
Order By: Relevance
“…In death by asphyxiation or drowning, there is an accumulation of blood in the tooth pulp due to either a rapid increase in venous pressure to the head, or a pooling of blood in the head and neck region due to the victim lying in a head-down position after death (Clark and Law, 1984;Borrman et al, 1994). Studies also show that the discoloration is often confined to the incisors, canines, and premolars (Kirkham et al, 1977), as was found here.…”
Section: Burial Descriptionsupporting
confidence: 74%
See 1 more Smart Citation
“…In death by asphyxiation or drowning, there is an accumulation of blood in the tooth pulp due to either a rapid increase in venous pressure to the head, or a pooling of blood in the head and neck region due to the victim lying in a head-down position after death (Clark and Law, 1984;Borrman et al, 1994). Studies also show that the discoloration is often confined to the incisors, canines, and premolars (Kirkham et al, 1977), as was found here.…”
Section: Burial Descriptionsupporting
confidence: 74%
“…This is internal to the tooth structure and not on the enamel, so is not due to diet. Previous research into the cause of pink teeth (Beeley and Harvey, 1973;van Wyk, 1988avan Wyk, , 1989Watts and Addy, 2001) have isolated the source of this discoloration to some kind of hemoglobin which has diffused into the dentin (Kirkham et al, 1977;van Wyk, 1988b;Fish, 2005). While pink teeth are not correlated exclusively with one cause of death, it is most commonly found in conjunction with death by drowning (Clark and Law, 1984;Brøndum and Simonsen, 1987;van Wyk, 1987;Pollanen, 1998).…”
Section: Burial Descriptionmentioning
confidence: 99%
“…While he made his observations in cases of drowning and hanging, Miles et al (1953) stressed the occurrence of this phenomenon in cases of strangulation and carbon monoxide intoxication in connection with the Christie murder case. However, the pathognomic value of pink teeth is more than doubtful since it has been described in a variety of unnatural causes of deaths (Van Wyk 1987;Kirkham et al 1977;Borrman et al 1994). We report the occurrence of pink teeth in the corpse of a female because similar changes in colour were also found in the fingernails.…”
Section: Introductionmentioning
confidence: 70%
“…8,18 The pink-tooth phenomenon was duplicated experimentally in vitro by using cadaver blood and human teeth divided longitudinally 19 or by instilling into the pulp chambers whole blood and blood with the red cells hemolyzed. 2,11 Forensic pathologists must have observed that the distribution of pink teeth can vary in a mouth and not all teeth are necessary involved. 18,19 In previous studies, not all jaws and/or teeth may have been examined thoroughly, and we still do not know the real frequency and distribution of the phenomenon.…”
mentioning
confidence: 99%